Теоретические аспекты механизма государственной поддержки производителей продукции животноводства - Аманов, Батыр; Плевако, Ярослав Владимирович; Гудэнко, Алина Александровна (НТУ "ХПИ", 2016)
Исследованы теоретические аспекты механизма государственной поддержки аграрного сектора. Проанализированы основные проблемы господдержки производителей продукции животноводства. Предложено авторское определение государственной поддержки. Доказано, что комплекс социально-экономических, законодательно-правовых, организационных и социальных мер, осуществляемых государством, должен быть направлен на эффективное и устойчивое развитие производителей продукции и сельских территорий с целью обеспечения продовольственной безопасность страны.

Investigated the theoretical aspects of the mechanism of state support of the agricultural sector. Analyzed the main problems of state support of livestock producers. Proposed by the author's definition of the state support. Been proven that the complex of socio-economic, legislative, legal, institutional and social measures implemented by the state, should be directed to the efficient and sustainable development of producers and rural areas to provide food security of the country. State support system should be implemented based on these principles: equal access t o state support for all business entities regardless of their organizational-legal form and size; targeted nature of reception and use of budgetary funds; targeting of state support; efficient use of funds. The main forms of implementation of the state support for livestock producers could be subsidies for the production, material and technical resources, subsidizing lending to the direct producers of livestock production, subsidies for capital expenditure, the budgetary allocation for science and other forms of direct and indirect state support.
Theoretical aspects of mechanism of government support for animal husbandry producers
Keywords: государственная поддержка; меры; производители продукции животноводства; устойчивое развитие; продовольственная безопасность; state support; measures; producers of livestock production; sustainable development; food security